ANALISIS UPAYA STRATEGI PEMASARAN DINAS KOPERASI USAHA KECIL MENENGAH DAN PERDAGANGAN KOTA PEMATANGSIANTAR DALAM MENINGKATKAN HASIL PENJUALAN PRODUK UKM TENUN ULOS DI KOTA PEMATANGSIANTAR - Idia Fhitri Syawalina; Ahnis Zulkarnain; Muhammad Zufri; Pipfhan Syahuri Srg; Fahry Alamsyah (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2021)
This research discusses about the influences of product, price, and promotion as marketing strategies in increasing sales volume of UKM product at Pematangsiantar City. The aim of this research is to analyse the influences of product, price, and promotion both partially and simultaneously on product sales volume at the office. This is   a quantitative research with random sampling technique. The sample is 74 cosumers. Results show that each independent variable; product, price, and promotion, partially influences product sales volume positively  and  significantly.  product  has  tcount    value  6,853     and  level  of significance 0.000, price has 3,522 and 0.001, and promotion has 4,238 and 0.000. Simultaneously, product, price, and promotion have significant and positive influences in increasing sales volume of UKM product at Pematangsiantar City with Fcount value 64,813 and level of significance 0.000.